2013
DOI: 10.1016/j.immuni.2013.08.029
|View full text |Cite
|
Sign up to set email alerts
|

CD301b+ Dermal Dendritic Cells Drive T Helper 2 Cell-Mediated Immunity

Abstract: Summary Unlike other types of T helper (Th) responses, whether the development of Th2 cells requires instruction from particular subset of dendritic cells (DCs) remains unclear. By using an in vivo depletion approach, we have shown that DCs expressing CD301b were required for the generation of Th2 cells after subcutaneous immunization with ovalbumin (OVA) along with papain or alum. CD301b+ DCs are distinct from epidermal or CD207+ dermal DCs (DDCs) and were responsible for transporting antigen injected subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
423
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(455 citation statements)
references
References 62 publications
31
423
1
Order By: Relevance
“…However, recent advances revealed that Tfh cells, rather than Th2 cells or other Th subsets, are important for controlling humoral immunity (43). In addition, previous studies reported the differential regulation of Th2 cell development and Tfh cell-controlled IgE production (43,44). In the current study, Tfh cell development was abrogated in Myd88 2/2 mice with ragweed pollen exposure in the lung.…”
Section: Discussionmentioning
confidence: 43%
“…However, recent advances revealed that Tfh cells, rather than Th2 cells or other Th subsets, are important for controlling humoral immunity (43). In addition, previous studies reported the differential regulation of Th2 cell development and Tfh cell-controlled IgE production (43,44). In the current study, Tfh cell development was abrogated in Myd88 2/2 mice with ragweed pollen exposure in the lung.…”
Section: Discussionmentioning
confidence: 43%
“…As mentioned above, Langerin + dDCs are shown to induce 1 cells during cutaneous Candida albicans infection [44]. On the other hand, in the sensitization phase of CHS, various literatures indicate the importance and redundancy of di erent DC types, including LCs, Langerin + dDCs, and CD11b + cDCs [45,52,55,56]. e hapten dose and the number of DCs seem to be important, as discussed in the chapter of LCs.…”
Section: Dermismentioning
confidence: 93%
“…XCR1 + cDCs are the only subset to express high levels of Langerin/CD207 among dDCs, and are o en called as Langerin + dDCs. LCs and CD11b -cDCs are also shown to express CD301b, also known as macrophage galactose C-type lectin type 2 (Mgl2) [45,52]. Other several di erent surface markers are used to distinguish each population (Tab.…”
Section: Dermismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the intestine-specific DC population co-expressing CD11b and CD103 is involved in priming Th2 responses during Nippostrongylus brasiliensis infection. Alongside, cutaneous CD11b + DCs induce polarization of Th2 cells after subcutaneous immunization with ovalbumin along with papain or alum, as well as in a model of contact hypersensitivity [14][15][16]. In two of these studies [15,16], the macrophage galactose-type C-type lectin 2 (MGL2/CD301b) was used as a surrogate marker for CD11b + DCs.…”
mentioning
confidence: 99%